Insights into gold nanoparticles as a mucoadhesive system - Ouellette, Mathieu (Sci Rep, 2018)
A large number of drugs are administered on different mucosal surfaces. However, due to the poor mucoadhesion of the current formulations, their bioavailability is often very low. The development of efficient mucoadhesive drug delivery systems is thus crucial for improving the performance of these drugs. The mucoadhesive properties of gold nanoparticles were investigated. First, two types of gold nanoparticles were synthesized: AuNP1 and AuNP2. AuNP1 only contain internal thiol groups on their metallic core, and AuNP2 contain both internal and peripheral thiol groups. Different protocols based on an adapted quantitative colorimetric method, UV-visible and fluorescence spectroscopies were then developed to gather information on their mucoadhesive properties. Moreover, a global correction factor for the inner filter effect in spectrofluorimetry was proposed, and the data obtained were compared to those commonly used in the literature. Mucins deeply interact with AuNP1, perturbing their core, whereas they remain at the periphery of AuNP2. The quantitative method suggests that a larger number of mucins interact with AuNP2. The establishment of this protocol could be applied to assess the mucoadhesive properties of other stable molecules. This mucoadhesive property of gold nanoparticles could be combined with their drug delivery ability in order to improve the medication administered on mucosa.